“LIVING NIRBHAYA: TOWARDS A VIOLENCE FREE SOCIETY” - Editor (Asian Horizons, 2013)
The third National Consultation on Gender Relations in the Church and Society organized by Streevani Pune, in collaboration with Satyashodhak, IWTF (Indian Woman Theologians Forum) and Montfort Social Institute from 9th – 11th August at Atmadharshan, Andheri (E), Mumbai was on the theme “Living ‘Nirbhaya: Towards a Violence Free Society’”. There were 44 participants consisting of Priests, Women and Men Religious and Laity from across the country. Archbishop Dominic Lumen of Imphal, Chair Person of the CBCI office for Women and Bishop Agnello Gracias, Auxiliary Bishop of Mumbai Archdiocese and Sr Rita Pinto RSCJ, National President of CRI Sister’s Section encouraged the group with their participation.